MDGS AS AN INSTRUMENT OF HEGEMONY: A NEW TYPE OF HEGEMONIC TRANSFORMATIVE FOR VANISHING PLURALITY OF RESISTENCE MOVEMENTS IN INDONESIA - Purnomo, Joko (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
Since 1990s, development discourse has been focused into the fulfillment of Millennium Development Goals (MDGs). With the help from western countries, international development agencies and international financial institutions, MDGs have raised its popularity in developing country and steering the development agenda of developing country. The increase in the use of MDGs as a development goal in developing country, however, can not be seen solely as a triumph of liberal developmentÂ approach on how developing country solve their own development problems. It can also be seen as (ones again) a winning of liberal hegemonic system in the battle for hegemony over its opponents. Hence, the story so far is still the same: developing country is in the hand of developed country.Key words: Capitalism, Development, MDGs, resistence movements, hegemony